Biological control of rice sheath blight disease with formulation of indigenous Trichoderma strains under paddy field conditions - Naeimi, Shahram; Khosravi, Vahid; Nouri, Mohammad-Zaman; Hoda, Hassan; Vágvölgyi, Csaba; Kredics, László (Acta Biologica Szegediensis, 2019)
The effectiveness of indigenous Trichoderma strains in preventing sheath blight disease was evaluated during two growing seasons under paddy field conditions. Broom sorghum seeds were used for mass production of Trichoderma strains. Colonized seeds were ground to powder and mixed with talc and carboxymethyl cellulose. Suspensions were made from the bioformulations and sprayed onto rice plants. Effects of Trichoderma strains on disease incidence and severity as well as yield and other growth parameters were determined and compared with a chemical fungicide and a commercial biofungicide. A combined analysis of variance across two years was performed and a statistically significant effect of year, treatment and their interaction was reported. Results indicate that environmental factors and different biological fungicides had a strong effect on disease development under natural conditions. According to the results, propiconazole and T. harzianum AS12-2 resulted in the least disease severity and incidence. Overall, the efficacy of T. harzianum AS12-2 in reducing sheath blight development was significantly better than other Trichoderma treatments and was comparable to the conventional fungicide.